WORKING TIME AND REST TIME OF REMOTE EMPLOYEES - Ruziyev Dostonbek (European Science Publishing, 2024)
It is dedicated to the study of the introduction of this method of remote work, the features of interaction between the remote employees and the employer, the procedure and specific aspects of the regulation and organization of the work of remote employees.
Keywords: Remote employee, remote work, vacation time, working time, network, network employee.